FRI0431 Fatigue Is A Determinant of Reduced Work Productivity in Ankylosing Spondylitis: Results from A Prospective Cohort Study. (15th July 2016) - Basu, N.; Druce, K.; Aikman, L.; Dilleen, M.; Barata, T.; Burden, A.; Szczypa, P.
Abstract : Background: Work disability is a critical issue for patients with ankylosing spondylitis (AS). In the general population, fatigue is a principal determinant of reduced work productivity. This potentially modifiable risk factor has yet to be investigated in AS. Objectives: To investigate the relationship between fatigue and work productivity among AS patients. Methods: Data were obtained from an observational study which followed a large German cohort of AS patients treated with etanercept as part of routine clinical practice between October 2007 and May 2014. The exposure of interest, fatigue (Bath Ankylosing Spondylitis Disease Activity Index subscale, BASDAI), was collected at baseline (at etanercept commencement) and 6 months. Putative confounders were also evaluated at these time-points: age, gender, pain (visual analogue scale, VAS), depression (EQ5D item), physician's disease activity assessment (VAS) and C-reactive protein (CRP). The primary outcome, work productivity loss, was measured using subscale 3 of the Work Productivity and Activity Index: Specific Health Problem (WPAI: SHP). Two stepwise ANCOVA models (adjusted for confounders and baseline work productivity loss) were developed to examine: 1) the association between baseline fatigue and 6 month work productivity loss; 2) the association between change in fatigue and change in work productivity loss (baseline to 6 months). Results: Of the n=1663 study participants included in the analysis population, n=1003 (60%) were in employment at baseline: mean (SD) age 40.7 (10.6) years, 63.3% male, mean (SD) disease duration 7.3 (7.8) years at baseline. At 6 months, 837 contributed to the analyses of which 93% remained on etanercept therapy. Following adjustment of putative confounders, baseline fatigue was significantly associated with work productivity loss at 6 months (p=0.035, see table). Similarly, the change in fatigue levels between baseline and 6 months was independently associated with a change in work productivity loss (p=0.044, see table). Conclusions: In AS patients receiving etanercept therapy, high levels of fatigue are predictive of future work productivity loss. Furthermore, reductions in fatigue are significantly associated with improvements in work productivity. Together, these data support a potential causal role for fatigue in AS related work disability. Acknowledgement: Joachim Sieper, Charité University Berlin, the Principal Investigator of study B1801087 Disclosure of Interest: N. Basu Grant/research support from: Pfizer i-CRP grant, Speakers bureau: Non-promotional lectures, K. Druce: None declared, L. Aikman Shareholder of: Pfizer stock, Employee of: Pfizer, M. Dilleen Shareholder of: Pfizer stock, Employee of: Pfizer, T. Barata Consultant for: Contracted by Pfizer to provide statistical input, A. Burden Consultant for: Paid by Pfizer to provide statistical support, P. Szczypa Shareholder of: Pfizer stock, Employee of: Pfizer